2020
DOI: 10.1007/s10311-020-01007-8
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution: new bio-based ionic liquids absorb both hydrophobic and hydrophilic volatile organic compounds with high efficiency

Abstract: Emission of volatile organic compounds (VOCs) in the atmosphere is a major health concern for the World Health Organization (WHO). For instance, more than 4 million premature deaths are attributed yearly to outdoor air pollution, thus calling for advanced remediation techniques. Absorption systems using solvents are commonly used to remove air pollutants, yet efficiency is limited by a solvent property, which is either hydrophilic or hydrophobic. As a consequence, classical solvents are not able to capture bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 36 publications
0
20
1
1
Order By: Relevance
“…As we have already prepared ILs with levulinate, lactate, and prolinate anions with other cations such as TBA and TBP , or cholinium esters, , we chose to compare the toxicity of all these ILs with the betaine amide derivatives described in this study. Thus, a structure/toxicity relationship could be established according to the nature of the cations and anions.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…As we have already prepared ILs with levulinate, lactate, and prolinate anions with other cations such as TBA and TBP , or cholinium esters, , we chose to compare the toxicity of all these ILs with the betaine amide derivatives described in this study. Thus, a structure/toxicity relationship could be established according to the nature of the cations and anions.…”
Section: Resultscontrasting
confidence: 77%
“…All these ILs have been fully characterized (NMR, IR, elemental analysis, and TGA), which showed decomposition temperatures over 250 °C except for those with prolinate, as previously described for TBA or TBPbased ILs. 12,14 As we have already prepared ILs with levulinate, lactate, and prolinate anions with other cations such as TBA and TBP 12,14 or cholinium esters, 15,16 we chose to compare the toxicity of all these ILs with the betaine amide derivatives described in this study. Thus, a structure/toxicity relationship could be established according to the nature of the cations and anions.…”
Section: ■ Results and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Before we attain a solid understanding on this matter, several precautionary measures may be worth considering to mitigate the risks of inhaling virus-laden droplets and particles rising from the floors and lower regions of the indoor atmosphere under the constant uprising airflows induced by human thermal plume. Where practical, removing carpeting and keeping floors clean and disinfected, eliminating sources of indoor aerosol emissions (e.g., tobacco smoking, laser printing), maintaining adequate natural ventilation to reduce aerosol accumulation (Gennaro et al 2014 ) and using air purification methods (Fahri et al 2020 ; Gopinath et al 2018 ) would all be effective methods to mitigate such risks. For sedentary individuals, moving their body closer to desk can partly block the uprising thermal plume and reduce its velocity entering the breathing zone (Melikov 2015 ; Licina et al 2014 ).…”
Section: Influences Of Human Thermal Plumes On Transmission Of Airbormentioning
confidence: 99%
“…Based on this, Yu et al introduced π-electron donors into common imidazolium-based ILs and found the functional ILs showed better toluene absorption performance. Although the imidazolium-based ILs show good toluene absorption performance, many of them are toxic and even carcinogenic. In Fahrl and co-workers’ work, the biobased ILs were synthesized from choline chloride (ChCl) and fatty acids, and the vapor–liquid partition coefficient of toluene in the bio-based ILs can be 156 times more than that in water. Admittedly, ILs are one of the most promising solvents for toluene absorption; however, the synthesis of most ILs is complex and expensive, which limits their practical application. , …”
Section: Introductionmentioning
confidence: 99%